2020
DOI: 10.2147/mder.s234156
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Novel, Easy-to-Use Staple Line Reinforcement for Surgical Staplers</p>

Abstract: Background: Staple line reinforcement (SLR) is a popular tool used by surgeons to increase staple line strength and improve peri-operative hemostasis. However, currently marketed buttress materials require special attention in attachment to the staple anvil and cartridge and may come loose during typical maneuvering of stapling procedures. We have evaluated a new SLR that has an attachment material that affixes buttress across the entire anvil and cartridge face to prevent slipping, twisting, sliding and/or bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…7 A previous study evaluated the safety of a stapler with preattached buttress material and found that there were no cases of bleeding >50 mL that required intervention of the staple line, and only three cases (8%) experienced minor leaks that were treated conservatively. 6 Regarding the application of stapling devices in hepatic surgery, it was considered that an SLR technique with an absorbable polymer membrane or radiofrequency ablation assistance may be needed for the safe application of stapling devices in liver surgery. Overall, the benefits of using staple line reinforcement during hepatectomy are increased staple line strength and improved perioperative hemostasis, which can reduce the risk of complications such as leaks or bleeding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7 A previous study evaluated the safety of a stapler with preattached buttress material and found that there were no cases of bleeding >50 mL that required intervention of the staple line, and only three cases (8%) experienced minor leaks that were treated conservatively. 6 Regarding the application of stapling devices in hepatic surgery, it was considered that an SLR technique with an absorbable polymer membrane or radiofrequency ablation assistance may be needed for the safe application of stapling devices in liver surgery. Overall, the benefits of using staple line reinforcement during hepatectomy are increased staple line strength and improved perioperative hemostasis, which can reduce the risk of complications such as leaks or bleeding.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, SLR also has a lower risk of bleeding, which can potentially lead to a reduction in intraoperative and postoperative complications. 6 The complete absorption of PGA within approximately 15 weeks further underscores its safety. Beyond liver resection, SLR has been used in various surgical contexts, including thoracic surgery, 7 upper gastrointestinal reconstruction, 8 and pancreatic resection, 9 as well as in animal experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Absorbable materials, such as polyglycolic acid or polyglactin, provide temporary reinforcement and are eventually absorbed by the body ( 13 , 14 ). Overall, buttressing distributes tension evenly across the staple line and provides a broad pressure profile around the individual staples, reducing staple line dehiscence and improving hemostasis ( 15 ).…”
Section: Introductionmentioning
confidence: 99%